Penyusunan Media Informasi Tentang Lama Persalinan Kala 2 dan Manfaat Senam Hamil - Yuliaji Siswanto; Mona Saparwati; Sigit Ambar Widyawati (Universitas Ngudi Waluyo, 2019)
Prolonged labor causes of prenatal death, two and a half times bigger than normal birth. Some researches show that pregnancy gymnastic can shorten the second stage of labor,Â the gymnastic decrease the incidences of birth which need a further treatment four times, also decrease the stimulation in the first stage of labor as four and a half times. This research aims to develop an information media about pregnancy gymnastic for the pregnant women. The method was action research. First step, found the condition and comprehension level of the pregnant women about the second stage of labor and the advantages of pregnancy gymnastic, then compiled an information media. The second step did the premodel implementation (action), then finishing the model of media became to leaflets. Furthermore, leaflet effectiveness tests were carried out on 58 pregnant women, and the results were analyzed by the Wilcoxon test. Some respondents have less comprehension (73,3%) about the duration of the second stage of labor and the advantages of pregnancy gymnastic. Based on the results, the researcher made a model information media in the form of leaflet containing Â the stages of labor and pregnancy exercise. Based on the results of the data analysis, there were significant differences in the level of knowledge before and after giving leaflets about the stages of labor and pregnancy exercise in pregnant women (p <0.00001).